(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
Throughout the 18th century the town of Orizaba was building an image of devote city. Image derived from the dense fabric of religious corporations that characterized its urban space, was also one of the reasons for pride of local patriotism, an argument in the dispute of civil corporations, and local demands to the Crown. However, the piety and devotion from the people of Orizaba were questioned in the press in early 19th century, forcing the local elite to build a new image of the village, related to the promotion of the lights, both culturally and in the renewal of the urban space. However, the politicization of first federalism brought criticisms back, increasingly stronger to the village of Orizaba, earlier praised by devotee and now despised by “fanatical”. This process clearly illustrates how the position of religion was transforming into public opinion and pathways that secularization was building.